PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PABRIK ROTI AGUNG KABUPATEN TASIKMALAYA - Ernawati; Gia Fitra Buana Sidik (Cipasung Techno Pesantren: Jurnal Ilmiah, 2022)
This study discusses the importance of product quality for purchases at the Roti Agung factory in Tasikmalaya Regency. The research method used in this research is a descriptive analysis method, while the procedure for data discussion is carried out by field study interviews, questionnaires, observations and documentation. Test equipment used in data processing using simple linear regression test, test, determination test, non-determination test, validity test, reliability test, and hypothesis testing. Based on the results of the value of r = 0.718 shows a strong influence between product quality variables with a significant positive positive purchasing decision between product quality and purchasing decisions at the Bread Factory, which is equal to t count > t table or 6.41 > 2.02 meaning Ho is rejected Ha accepted.